The Influence of Copper on Halogenation/Dehalogenation Reactions of Aromatic Compounds and Its Role in the Destruction of Polyhalogenated Aromatic Contaminants - Weidlich, Tomáš (MDPI, 2021)
The effect of copper and its compounds on halogenation and dehalogenation of aromatic compounds will be discussed in the proposed article. Cu oxidized to appropriate halides is an effective halogenation catalyst not only for the synthesis of halogenated benzenes or their derivatives as desired organic fine chemicals, but is also an effective catalyst for the undesirable formation of thermodynamically stable and very toxic polychlorinated and polybrominated aromatic compounds such as polychlorinated biphenyls, dibenzo-p-dioxins and dibenzofurans accompanied incineration of waste contaminated with halogenated compounds or even inorganic halides. With appropriate change in reaction conditions, copper and its alloys or oxides are also able to effectively catalyze dehalogenation reactions, as will be presented in this review.
Vliv mědi na halogenaci/dehalogenaci aromatických sloučenin a role mědi na rozklad polyhalogenovaných aromatických kontaminantů
Keywords: halogenation; oxybromination; oxychlorination; copper-catalyzed; arylation; Ullmann reaction; coupling; hydrodehalogenation; halogenace; oxybromace; oxychlorace; arylace; Ullmannova reakce; hydrodehalogenace